Phrasal verbs as elements of the locutionary frame - Martínez López, Juan A. (2024)
The present study takes as its starting point the exclusion that phrasal verbs traditionally have experienced in the field of phraseological studies, and more specifically, those carried out in the sphere of locutions. In order to determine if the mentioned exclusion has been correct, we have carried out a detailed analysis of a corpus of 50 phrasal verbs, in light of the academic debate that during the last decades has been establishing the main defining criteria of the phrases. The criteria mentioned have been two of a formal nature, such as multiverbality and fixation, and one semantic, the idiomaticity of the whole structure. After this analysis, we have been able to verify that, with certain formal peculiarities typical of these verb+preposition as the propositional reaction and its role as an attachment to the verb, phrasal verbs fully meet the defining criteria.